2004
DOI: 10.1103/physrevb.69.035318
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effect in two-photon excited luminescence from silver nanoparticles

Abstract: A direct manifestation of electron energy quantization in metal nanoparticles is observed in two-photon excited luminescence. Experiments reveal the discrete spectra in broadband anti-Stokes photoluminescence from aggregates of silver colloid particles. A theory based on a spherical quantum-well model for metal nanoparticles is in good agreement with experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
3
39
1
Order By: Relevance
“…Additionally, metal nanoparticles are advantageous with the ability to tailor the absorption band by modifying the particle geometry (nanospheres, nanoshells, nanorods, nanostars) for specific applications. Both single-photon and multiphoton PL of metal nanoparticles have been shown to correlate strongly with their plasmon resonances [148,[151][152][153], and they have both been applied to biological imaging.…”
Section: Inherent Pl Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, metal nanoparticles are advantageous with the ability to tailor the absorption band by modifying the particle geometry (nanospheres, nanoshells, nanorods, nanostars) for specific applications. Both single-photon and multiphoton PL of metal nanoparticles have been shown to correlate strongly with their plasmon resonances [148,[151][152][153], and they have both been applied to biological imaging.…”
Section: Inherent Pl Emissionmentioning
confidence: 99%
“…Here, we focus on inherent nonlinear signals from the NSOM tip. It is found that, when a sharp gold tip is excited with 780 nm femtosecond pulses, nonlinear inherent PL, as well as SHG, is generated [152,168]. The inherent emission spans across the visible and NIR regions, forming a highly confined white-light continuum…”
Section: Near-field Imaging By Inherent Nonlinear Emissionsmentioning
confidence: 99%
“…Metal nanoparticles are also capable of photoluminescence, which has been shown to correlate strongly with their welldefined plasmon resonances (10)(11)(12)(13)(14)(15)(16). For example, Mohamed et al (11) have observed that the quantum efficiency of singlephoton luminescence from gold nanorods is enhanced by a factor of Ͼ1 million under plasmon-resonant conditions.…”
mentioning
confidence: 99%
“…The much weaker and broader band at longer wavelengths is from two-photon excitation induced luminescence of the Ag particles. [19][20][21][22] The emission spectrum in Fig. 1 can be empirically described by a nonlinear leastsquares fit using a sum of a squared Gaussian function for the 400 nm peak, as the SH intensity is expected to be proportional to the square of the Gaussian profile of the fundamental intensity and a Gaussian function for the two-photon luminescence.…”
mentioning
confidence: 99%